2018
DOI: 10.1108/ilt-01-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roller dynamic unbalance on cage stress of high-speed cylindrical roller bearing

Abstract: Purpose The purpose of this study is to investigate the effect of roller dynamic unbalance on cage stress. Design/methodology/approach Considering the impact of roller dynamic unbalance, the dynamic analysis model of high-speed cylindrical roller bearing is established. And then the results of dynamic model are used as the boundary conditions for the finite element analysis model of roller and cage to obtain the cage stress. Findings Roller dynamic unbalance affects the contact status between roller and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…ð Þ are the contact and frication force between the roller and the cage, when the roller contact directly with the pocket beam, the forces calculated by the Hertz contact theory, and the roller does not directly contact with the pocket, only calculate the fluid force; F, B indicate the front and back cross beam of cage pocket, respectively; M j c is the torque between the roller and the cage due to roller skew; M j d is the additional moment due to the drag force; M j mis is the torque between the roller and the raceway due to roller tilt; j j is the roller tilt angle; g j is the roller skew angle; the calculation processes of these forces and moments according to Cui et al (2017Cui et al ( , 2018aCui et al ( , 2018b; T j rcy is the churning moment due to the oil-gas acting on the cylindrical surface of the roller; T j rland is the churning moment due to the oil-gas acting on the end face of the roller, according to Gupta (1984).…”
Section: Dynamic Analysis Model Of Bearing With Cage Dynamic Unbalancementioning
confidence: 99%
See 1 more Smart Citation
“…ð Þ are the contact and frication force between the roller and the cage, when the roller contact directly with the pocket beam, the forces calculated by the Hertz contact theory, and the roller does not directly contact with the pocket, only calculate the fluid force; F, B indicate the front and back cross beam of cage pocket, respectively; M j c is the torque between the roller and the cage due to roller skew; M j d is the additional moment due to the drag force; M j mis is the torque between the roller and the raceway due to roller tilt; j j is the roller tilt angle; g j is the roller skew angle; the calculation processes of these forces and moments according to Cui et al (2017Cui et al ( , 2018aCui et al ( , 2018b; T j rcy is the churning moment due to the oil-gas acting on the cylindrical surface of the roller; T j rland is the churning moment due to the oil-gas acting on the end face of the roller, according to Gupta (1984).…”
Section: Dynamic Analysis Model Of Bearing With Cage Dynamic Unbalancementioning
confidence: 99%
“…However, they did not study the cylindrical roller bearing as well as the axial excursion of unbalance. Cui et al (2017Cui et al ( , 2018aCui et al ( , 2018b investigated the influence of roller dynamic unbalance on the bearing's characteristics such as the cage stability and the cage fatigue stress. However, only the roller unbalance's influence was considered and the cage was regarded as ideal structure.…”
Section: Introductionmentioning
confidence: 99%
“…According to failure case analysis and statistics, cage fatigue fracture is one of the serious failure forms of highspeed cylindrical roller bearings. e whirl of the cage and frequent collision and friction between rollers and cage are the main causes for cage failure [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Mostafa et al (2019) reported that the damage of a bearing usually occurs in the lintel of the cage, and the cage broken is one of the important reasons of bearing failure in high-speed machinery. Cui et al (2019) reported that the unbalance of the cage would influence the instability of the cage motion. Liu (2011) indicated that the bearing failure resulting from the skidding and instability of the 0cage accounts for 25 per cent of the total failure of the rolling bearings.…”
Section: Introductionmentioning
confidence: 99%